A Review: Graphene Modified Polymer Coatings For Corrosion Protection. Issue 1 (June 2021) - Kumari Ola, Saraswati; Priyanka,; Soni, Saloni; Dhayal, Veena; Singh Shekhawat, Dalip
Abstract: Environmental and other chemical factors lead to decimated corrosive behaviour of metallic materials that is a severe hazard and an emerging challenge for times. Different protection strategies have been proposed to suppress this problem and among them graphene based coatings are considered to be great technique against corrosive behaviour because of its hydrophobic properties and ability to provide corrosion resistance of composite material. The incorporation of functional nanoparticles can provide the corrosion resistance to mild steel. It regarded a promising nonmaterial in corrosion protection. Present written text focuses on the preventive applications of graphene based nanomaterials, nanocomposites, polymeric coating techniques and their methods to fight the corrosive act of steel.